Exploring Culturally Responsive Teaching Clusters in Indonesian Higher Education EFL Contexts: Patterns and Students’ Perspectives - Movi Riana Rahmawanti; Syifa Dwi Handayani; Amalul Umam; Rindudinnia Aidaintan; Indah Sri Redjeki (PANYONARA: Journal of English Education, 2026)
Numerous studies have indicated that Culturally Responsive Teaching promotes inclusivity, increases student engagement, builds learners’ confidence, and fosters meaningful EFL learning. This study examines the implementation and impact of Culturally responsive teaching (CRT) in Indonesian EFL classroom focusing on identifying specific CRT clusters. The research aims to determine the types of CRT clusters manifested in classroom practices and to analyze students’ perceptions and responses toward CRT Practices over one semester. Employing a qualitative-dominant mixed-methods design, the study integrates descriptive quantitative analysis with in-depth qualitative inquiry. Quantitative data were derived from 20 students’ reflective journals by calculating the frequency of CRT practices and categorizing them into Clusters A, B, and C. Qualitative data were collected through semi-structured interviews from 12 participants and journal analysis to explore students’ experiences on Culturally responsive teaching. The findings reveal that all three CRT clusters were meaningfully implemented, with Cluster B—creating an inclusive, safe, and supportive environment—emerging as the most dominant. Overall, CRT positively enhanced students’ confidence, engagement, and comprehension in English Learning.